Carbon foam electromagnetic mm-wave absorption in reverberation chamber. (April 2019) - Pastore, R.; Delfini, A.; Micheli, D.; Vricella, A.; Marchetti, M.; Santoni, F.; Piergentili, F.
Abstract: The electromagnetic (EM) absorbing cross section (ACS) of carbon foams in the mm-wave frequency range 50–70 GHz is analyzed by means of a reverberation chamber (RC) set-up. Carbon foams are lightweight cellular materials which are believed to provide benefits in EM interference/compatibility (EMI/EMC) issues, due to their significant thermo-mechanical and electrical properties. With respect to usually employed microwave test set-up, the range of frequency investigated allows to analyze the details of the foam bulk structure using shorter wavelengths. Moreover, the RC method allows to study the EM interaction with materials by taking into account not a single wave propagation mode (like in transmission line methods) but rather an homogeneous and statistically random EM field propagation. A full analysis of the material behavior can be thus carried out, by reproducing conditions similar to what really happens within operational environments. The foam EM properties are related to specific structural parameters, such as apparent density, open porosity, cell size/shape and 3-D arrangement. Significant ACS values are appreciated in low density foams; further, a functional dependence between EM mm-wave absorption capability and foam inner morphology is revealed, thus promoting the employed microwave set-up as effective method for supporting the structural analysis of porous materials. Graphical abstract: Image 1